Intramedullary locked nail for thumb fractures using finite elements. (13th August 2009) - Contreras, G.; Cerrolaza, M.; Gonzalez-Fuentes, C.
An intramedullary locked nail for metacarpal fracture treatment has been developed to provide an alternative for standard surgical techniques. It is minimally invasive allowing early post-operative hand movement. A 3D finite-element model was generated. Special attention was focused on the modelling of the thumb. Biomechanical testing and finite-element analyses were performed to determine the ultimate strength and the fatigue behaviour under physiological loads. The FEM was generated from the geometrical model of the nail-metacarpal assembly. Slight differences were observed when different materials were used. No critical stress were found for the 'in vivo simulation'. The system shows a sufficient strength.